2020
DOI: 10.14295/bds.2020.v23i1.1853
|View full text |Cite
|
Sign up to set email alerts
|

Fracture load of nano-ceramic composite material for anterior endocrown restorations

Abstract: Objective: To evaluate ability of Nano Ceramic Composite endocrown to withstand occlusal forces when used in the anterior region. Material and Methods: Eighty endodontically treated maxillary central incisors teeth were randomly divided into two main groups according to the restoration type.  40 of these teeth were post, core and crown restorations and 40 were endocrown restorations.  Then they were divided by halves into two subgroups according to the material used 20 were made with Lava Ultimate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…However, most of the studies states endocrown has better fracture resistance than post and crown. [7][8][9][10]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the studies states endocrown has better fracture resistance than post and crown. [7][8][9][10]…”
Section: Resultsmentioning
confidence: 99%
“…Endocrown is known as a minimally invasive type of restoration, which maintains as many healthy tooth structure as possible. 9 The success of endocrown is in the ability of adhesion of restoration material to the tooth surface. However, the use of appropriate materials can also affect the success of a restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The data were collected and included in table 2, the extraction of data from the included surveys was done by creating a standardized table in Excel with the following information: Author (year), Objective, Type of Study, Method, Experimental Groups, Dental Elements, Ferrule, Restoration Material, Aging. The level of scientific evidence was based on the classification of the "Oxford Center for Evidence-based Medicine", cited in the article by Demathé et al [16] observed in table 1. The extraction of all data was performed by the three reviewers and from the data obtained, tables were created in order to summarize the information.…”
Section: Discussionmentioning
confidence: 99%
“…Author (year), Grade of Recommendation and Level of Evidence according to the Oxford Level of Evidence[16] of the studies selected for review.…”
mentioning
confidence: 99%
“…Lise et al (Continues) higher load to failure for PCC, 2 and three studies showed no difference between groups. 4,9,10 In one study, 3 for teeth without ferule, ED led to similar endured cycles and load to failure than CC; however, CC with ferule outperformed ED without ferule.…”
Section: Data Extracted For Anterior Teethmentioning
confidence: 99%